Mangroves as unique but understudied traps for anthropogenic marine debris: A review of present information and the way forward - Luo, Ying Y.; Not, Christelle; Cannicci, Stefano (Environmental pollution (1987), 2021)
Marine debris and plastic pollution affect all coastal habitats, however coastal debris studies are predominantly performed on sandy beaches. Other coastal habitats, such as mangroves, remain understudied. Eighteen of the top twenty rivers that contribute the most plastic to the ocean are associated with mangroves, but very few of those forests were investigated in terms of plastic debris pollution. Here we discuss the results of the few available studies on macrodebris conducted in mangroves, which show that mangrove debris research is still in its early stages, with many areas of study to be further investigated. Indeed, the distinct structural complexity of mangroves increases their ability to trap debris from both terrestrial, freshwater and marine sources, resulting in impacts unique to the mangrove ecosystem. Our review highlights a significant lack in standardisation across the performed surveys. Here we suggest standardised guidelines for future integrated macrodebris and microplastic studies in mangroves to facilitate comparisons between studies. Such standardisation should prioritize the use of stratified random sampling, the measurement of the area covered by the debris and the abundance and type of macrodebris and microplastics found, in order to assess the ecological impact of macrodebris and its role as source of microplastics for adjacent ecosystems. We also advocate the use of standard categories across studies, based on those identified for surveying other coastal habitats. This review highlights an alarming knowledge gap in extent, sources and overall impacts of marine macrodebris, mainly constituted by plastic, on mangrove forests, which hinders policy making to address this issue. Standardised, reliable and extended research on this aspect of mangrove pollution is needed to manage and protect these endangered vegetated coastal ecosystems. [Display omitted] •Mangrove distribution overlaps with areas of severe plastic pollution.•Structural features of mangrove forests help them trap marine debris.•Marine debris impacts mangroves in unique ways compared to other coastal habitats.•Standardised sampling and surveys should be implemented in future studies.•More research needed on marine debris to manage and conserve mangroves.